Secondary minerals in the geyserites of the Geysers Valley (Kamchatka) - Sergeeva Anastasia; Kiryukhin Alexey (E3S Web of Conferences, 2019)
Secondary minerals assemblages that are deposited from thermal solutions at the top of geysers (Velikan, Bolshoy) were investigated. It is established that assemblages are represented mainly by opal and high-silica zeolites (mordenite and heulandite). As conditions of feeding hydrothermal reservoir change, minerals of the kaolinite group and smectites may appear.